Investigating a New Syllabus for Teaching UI Mobile App Design to Visual Communication Design Students in Amman, Jordan - Shahd Humaid,; Mustafa, Bahaa (Technium Social Sciences Journal, 2024)
Objectives: address the lack of specialized courses in user interface (UI) design for mobile applications in Jordanian universities' visual communication design curriculum. Develop an experimental educational syllabus for teaching UI mobile application design to visual communication design students in Jordanian universities. Methods: Four parts were used to structure the research: an introduction, the UI process, case studies and best practices, and a final project. Introduction: Basics of UI and UX Design. UI Process: theory, practice, tools, and publishing. Case Studies and Best Practices: Focus on medical UI mobile app design, including a UI checklist tool. Final Project: Students use free materials to present their work and review their projects with the class. Results:. The newly developed syllabus addresses the educational needs in UI mobile app design for visual communication design students. It emphasizes the importance of involving experts and practitioners in the design process. The syllabus provides comprehensive coverage of UI/UX design, practical tools, case studies, and project-based learning. Conclusions: The developed syllabus fills a critical gap in the visual communication design curriculum of Jordanian universities. It enhances students' knowledge and skills in UI mobile app design, better preparing them for the demands of the industry. The involvement of experts and practitioners is essential in creating effective educational programs in rapidly developing fields like mobile app design.